Трехуровневый преобразователь частоты с нулевой точкой и ШИМ-управлением фирмы "TWERD" для высоковольтного электропривода большой мощности - Тверд, Михаил; Яцукович, Рафал; Боневич, П.; Ткачук, Василий Иванович; Копчак, Любомир Стефанович; Копчак, Богдан Любомирович (НТУ "ХПИ", 2010)
The variant of three-level frequency converter with PWM-control for high-voltage and high-power electric drive is offered. Test results of MFC 810М frequency converter of 630 kW power (Uout=1150V) are given.
Three-level frequency converter with a zero point and PWM-control of "Twerd" company for high-voltage and high-power electric drive
Keywords: инвертор; напряжение; пространственная векторная модуляция; транзистор; индуктивность